Kajian Teologis terhadap Ajaran Hyper-Grace Joseph Prince - Fredy Simanjuntak (DIEGESIS: Jurnal Teologi Kharismatika, 2020)
Lately the topic of "grace" has also become a discussion and debate which is being discussed in the church environment. The term is also commonly called "modern grace" or "grace reform". The term is used by a number of teachers or characters in explaining their theological understanding of grace which they consider to be a new revelation of grace. The teaching of the gospel of grace does not refer to a particular church, but rather to theological teaching or understanding that is spreading very quickly to various churches throughout the world. There are some figures who write a number of books in their books describing the gospel teaching of grace, some of which are well-known and influential are Paul Ellis, Joseph Prince, Steve McVey, Clark Whitten and other gospel instructors of grace. Joseph Prince cannot be denied as one of these "grace" teachers who also influences the views of Christians in Singapore, America and Indonesia. AbstrakBelakangan ini topik mengenai “anugerah” (grace) juga menjadi diskusi dan perdebatan yang marak dibicarakan di lingkungan gereja. Istilahnya biasa juga disebut “kasih karunia modern” atau “Reformasi kasih karunia”. Istilah tersebut digunakan oleh sejumlah pengajar atau tokoh dalam menjelaskan pemahaman teologi mereka mengenai kasih karunia yang mereka anggap sebagai pewahyuan baru mengenai kasih karunia. Pengajaran tentang injil kasih karunia bukan merujuk kepada suatu gereja tertentu, tetapi lebih kepada pengajaran atau pemahaman teologi yang sedang merebak dengan sangat cepat ke berbagai gereja di seluruh dunia. Ada beberapa tokoh yang menulis sejumlah buku yang di dalam buku mereka menjelaskan pengajaran injil kasih karunia, beberapa diantaranya yang terkenal dan berpengaruh adalah Paul Ellis, Joseph Prince, Steve McVey, Clark Whitten dan pengajar injil kasih karunia lainnya. Tidak dapat disangkal Joseph Prince sebagai salah satu pengajar “anugerah” ini yang juga mempengaruhi pandangan orang-orang Kristen di Singapura, Amerika dan Indonesia.